Genetics and Epigenetics of Primary Biliary Cirrhosis - Bianchi, Ilaria; Carbone, Marco; Lleo, Ana; Invernizzi, Pietro (Seminars in Liver Disease, 2014)
Primary biliary cirrhosis (PBC) has been considered a multifactorial autoimmune disease presumably arising from a combination of environmental and genetic factors, with genetic inheritance mostly suggested by familial occurrence and high concordance rate among monozygotic twins. In the last decade, genome-wide association studies, new data on sex chromosome defects and instabilities, and initial evidence on the role of epigenetic abnormalities have strengthened the crucial importance of genetic and epigenetic factors in determining the susceptibility of PBC. High-throughput genetic studies in particular have revolutionized the search for genetic influences on PBC and have the potential to be translated into clinical and therapeutic applications, although more biological knowledge on candidate genes is now needed. In this review, these recent discoveries will be critically summarized with particular focus on the possible steps that may transfer genetic and epigenetic knowledge to direct health benefits in patients with PBC.
Keywords: primary biliary cirrhosis; genome-wide association study; sex chromosomes; immune-related pathways; novel drugs